An Analysis of Grammatical Errors in Writing Descriptive Texts Committed by the Tenth Grade Students of SMK Negeri 3 Singaraja in Academic Year 2016/2017 - ., Putu Rika Pramayani; ., Drs. I Wayan Suarnajaya,MA., Ph.D.; ., Dr. I Gede Budasi,M.Ed,Dip.App.Lin (Jurnal Pendidikan Bahasa Inggris undiksha, 2016)
Penelitian ini bertujuan untuk menyelidiki jenis-jenis kesalahan grammar yang dilakukan oleh murid-murid dikelas X TKJ 2 di SMK Negeri 3 Singaraja didalam menulis teks deskriptif dan menemukan sumber-sumber dari kesalahan grammar tersebut. Semua data dianalisis dengan menggunakan teori dari Azar dan Wakkad dalam mengelompokkan tipe-tipe kesalahan grammar yang dilakukan oleh siswa. Berdasarkan analisa dari data didalam penelitian ini, terdapat 16 jenis kesalahan yang dilakukan oleh siswa, diantaranya: add a word (25.52%), capitalization(12.41%), verb error (8.62%), pronoun (8.62%), spelling (7.93%), word order (6.55%), word choice (4.83%), singular/plural (5.86%), preposition (4.48%), omit a word (4.48%), meaning not clear (2.76%), word form (2.41%), punctuation (2.07%), article (1.38%), run-on-sentence (1.38%), and incomplete sentence (1.03%). Dalam sumber kesalahan, hasil dari penelitian ini diindikasikan bahwa sumber kesalahan terbanyak adalah kesalahan intralingual (65.77%).Kata Kunci : kesalahan grammar, menulis, teks deskriptif. This research aimed at investigating the types of grammatical errors committed by the students of class X TKJ 2 in SMK Negeri 3 Singaraja in writing descriptive text and finding out the sources of those grammatical errors. All data were analyzed by using Azar and Wakkadâs theory in classifying the types of grammatical error committed by the students. Based on the analysis of the data of this study, there were 16 types of errors committed by the students, which includes: add a word (25.52%),capitalization(12.41%), verb error (8.62%), pronoun (8.62%), spelling (7.93%), word order (6.55%), word choice (4.83%), singular/plural (5.86%), preposition (4.48%), omit a word (4.48%), meaning not clear (2.76%), word form (2.41%), punctuation (2.07%), article (1.38%), run-on-sentence (1.38%), and incomplete sentence (1.03%). In terms of error sources, the result of this study indicated that the major source of errors was intralingual error (65.77%).keyword : grammatical errors, writing, descriptive text.